Living Standards and Development Paths: Factory Systems and Job Quality during US Industrialization, 1790–1840 - Schneider, Benjamin (International review of social history, 2025)
Differences between models of industrialization are increasingly recognized as an important element of global economic history, and the quality of jobs is receiving new interest as a better indicator of living standards than income alone. This paper considers the implications of historical development models for job quality using the spinning section of textile manufacture in the early United States as a case study. The three factory systems that originated in Rhode Island, Massachusetts, and around Philadelphia varied in technical choice, management practices, and establishment size, and exhibited heterogeneity in components of job quality. The paper uses quantitative evidence, including more than 2000 observations of early industrial workers’ wages, qualitative material from government investigations, worker letters, and company correspondence, and the Historical Job Quality Indicators to analyse work quality for spinning workers and to explore variation between the three industrial models. Workers in the more competitive Philadelphia model had lower real earnings, less job security, and higher work intensity than employees of the paternalistic Massachusetts mills. The paper highlights the importance of considering variation by location when evaluating historical living standards and the implications of industrialization strategies for quality of life.